REHABILITATION OF PATIENTS WITH TRAUMATIC INJURIES OF THE CERVICAL SPINE OF MEDIUM DEGREE - Hreida, N. B.; Andriichuk, O. Ya.; Ulianytska, N. Ya.; Sitovskyi, A. M.; Lavryniuk, V. Ye. (Rehabilitation and Recreation, 2023)
The goal is to develop a comprehensive program of physical therapy for patients with moderate traumatic injuries of the cervical spine and to test it at various stages of rehabilitation. Material. Research methods: analysis of scientific and methodical literature; medical observations; orthopaedic research methods; dynamometry; collection of life and disease history; study of medical records, examination. In order to determine the effectiveness of the use of therapeutic exercises, the range of motion in the cervical spine was evaluated (when examining the patient, it was noted in which direction the amplitude of head and neck movements is limited and in which movements the pain increases). The results. Based on the results of orthopaedic research methods and dynamometry of traumatized patients with injuries of the cervical spine, justification of the effectiveness of the application of a complex program of physical therapy was carried out. In a gentle mode of anaesthesia, it is possible to perform breathing exercises and massage of the collar zone with the patient. The physical therapy program included therapeutic gymnastics, therapeutic massage, hydrokinesis therapy, mechanotherapy, myostimulation. In the recovery mode, the patients of the main group performed individually selected therapeutic exercises that helped relax the muscles of the cervical spine, shoulder girdle, and upper limb. The general principles of the physical therapy program were: regularity, systematicity and continuity of therapeutic exercises; strict individualization of exercises; their use according to the stage of the disease; strictly dosed increasing physical load in the training mode. Conclusions. Orthopaedic methods made it possible to determine the functional state of the musculoskeletal system of patients with traumatic injuries of the cervical spine, which made it possible to prove the effectiveness of the developed physical therapy program. Positive dynamics according to dynamometry indicators and all levels of the strength index were higher in the main group. Individually selected means of physical therapy accelerated the restoration of full functions of the cervical spine and increased the effectiveness of rehabilitation.